A new proof of Dávila–Flores–Guerra's result on existence of singular solutions. (February 2017) - Lai, Baishun; Wang, Jing
Abstract: Here we give a self-contained new proof of the existence of singular solutions to a class Dirichlet problem with a singular nonlinearity. These results were obtained by Dávila–Flores–Guerra (Dávila et al., 2009). Our proof is much more direct and simpler.